CoMFA based quantitative structure toxicity relationship of azo dyes - Pasha, F. A.; Nam, Kee Dal; Cho, Seung Joo (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2007)
Studies of relationship between structure and toxicity of azo dyes have been performed with comparative molecular field analysis (CoMFA) techniques. 3D QSTR analyses indicate that the steric and electrostatic interactions are important. The steric field based model gives strong correlation (q(2) = 0.57, r(2) = 0.92). The steric field in conjunction with electrostatic field give more strong correlation (q(2) = 0.57, r(2) = 0.95). All study indicates that a bulky and electronegative group at benzene ring and a small group at position 3 of aniline ring might be significant to reduce the mutagenicity.
Keywords: SEMIEMPIRICAL METHODS; 3D QSAR; DERIVATIVES; RAT; CARCINOGENICITY; MUTAGENICITY; OPTIMIZATION; PARAMETERS; FIELD; HELP